Analisis Gaya Belajar Siswa Berprestasi - Raden Dhea Fitrilia; Ratih Purnamasari; Yuyus Rustandi (FKIP UNIVERSITAS PAKUAN, 2021)
Analysis of Achieving Student Learning Styles. Qualitative research with a case study approach. Thesis of Primary School Teacher Education Study Program, Faculty of Teacher Training and Education, Pakuan University, Bogor, 2020. Aims to identify the dominant learning style possessed by an outstanding student at SDN Semeru 1 Bogor City named Muhammdan Rafa Setiawan and what factors affect the student's achievement. This type of research is qualitative with the case study method. Data collection techniques are carried out by interview, observation, and documentation. The results showed that students were less reactive to sound, easy to focus, quicker to understand new information by looking at it, were able to sit quietly during the lesson, answered verbal questions briefly to the point and liked learning activities by reading so it could be concluded that the dominant learning style the subject has, namely the visual learning style. Meanwhile, the factors that influence the subject's achievement are the presence of interest and high motivation to learn, have an unyielding and resilient attitude and support from the subject's teachers and parents.